Does environmental awareness improve business performance in property management? - David Kiki Baringin MT Samosir (Universitas Pamulang, 2022)
This research aims to assess the influence of Environmental Awareness on the Business Performance of property management in Indonesia. The data being used is primary data. The methodology used is the mixed method, where the quantitative approach is more dominant because the prioritized primary data is the questionnaire rather than interviews. The hypothetical test result indicates that Environmental Awareness significantly influences Business Performance, meaning that Environmental Awareness can increase the achievement of Business Performance. The invention from this study shows that property management should pay attention to profit and the planet, and the community surrounding the firm, showing that it is time for property management to run sustainably to increase competitiveness and develop more. Property management needs to implement Environmental Awareness to improve Business Performance.AbstrakPenelitian ini bertujuan untuk menelaah pengaruh kesadaran lingkungan terhadap kinerja bisnis perusahaan manajemen properti di Indonesia. Metodologi yang digunakan adalah metode campuran, dimana pendekatan kuantitatif lebih dominan karena data primer yang diprioritaskan adalah kuesioner daripada wawancara. Hasil pengujian hipotesis menunjukkan bahwa kesadaran lingkungan berpengaruh signifikan terhadap kinerja bisnis. Artinya, kesadaran lingkungan dapat meningkatkan pencapaian kinerja bisnis. Temuan ini menunjukkan bahwa manajemen properti harus memperhatikan profit dan planet, serta komunitas di sekitar perusahaan. Sudah saatnya manajemen properti berjalan secara berkelanjutan untuk meningkatkan daya saing dan lebih berkembang. Manajemen properti perlu menerapkan peduli lingkungan untuk meningkatkan kinerja bisnis